The Impact of Credit Rating Adjustments on Bond Spreads: Evidence from China - Kurbonov, Sinbad; Nasriddinov, Bobur; Mulbah, Kessellie Traore (European Scientific Journal, ESJ, 2024)
This paper investigates the impact of credit rating adjustments on bond spreads in the Chinese bond market, using a comprehensive dataset spanning from 2016 to 2022. Employing regression analysis and heterogeneity tests, the study explores the relationship between credit ratings, credit rating adjustments, and bond spreads, considering various control variables and the moderating effect of listing status. The findings reveal that credit rating adjustments significantly influence bond spreads, with upgrades narrowing spreads and downgrades widening them. Additionally, adjustments related to external support and firm performance were found to affect spreads, highlighting the importance of managing credit ratings for issuers. The study offers insights for investors, issuers, regulators, and academics, emphasizing the significance of credit rating information in investment decisions and market supervision. Overall, the research contributes to a better understanding of the dynamics between credit rating adjustments and bond pricing in China’s bond market, with implications for financial stability and economic development.